The North Texas Concussion Registry (ConTex) - C. Munro Cullum; Stephen Bunt; Cason Hicks; Nyaz Didehbani; Shane Miller; Bert Vargas; Tonia Sabo; Kathleen Bell; H Hunt Batjer (BMJ Open)
Purpose The North Texas Concussion Registry (ConTex) was established in 2015 as a multi-institutional collaboration intended to study risk factors, recovery patterns and clinical outcomes associated with concussion across the lifespan, with a particular emphasis on sport-related concussion.Participants Prospective enrolment of individuals who sustained a concussion within the past 6 months who were seen at one of four North Texas ConTex concussion clinics which employ common diagnostic criteria and assessment metrics to evaluate effects of a concussion as well as longitudinal tracking of recovery.Findings to date The ConTex database and multidisciplinary oversight team has been established, and over 1700 participants aged 5–88 years have been enrolled. A majority of concussions were sport-related (60%), with a mean age of 17.5 years and similar numbers of males and females. Three-month follow-up compliance has been excellent (86%), with a majority of subjects reporting good recovery by that time. ConTex has provided a rich data source for multiple research projects focused on concussion characteristics, risk factors and outcomes, and led to the development of a statewide youth concussion registry.Future plans ConTex data are being analysed to add to the body of knowledge regarding concussion mechanisms, factors related to recovery and improving outcomes for concussion patients. ConTex will serve as a platform for future treatment studies and may serve as a model for other concussion surveillance programmes.